Acoustic Evaluation of the Air-Conditioning Unit in the Room. (June 2019) - Králíček, J; Kučera, M
Abstract: This paper deals with an acoustic simulation, evaluation and measurement of an indoor air-conditioning unit commonly used in hotel rooms. The unit is situated in the plaster board ceiling of a hotel room above the entrance of the hotel room. The first step was to create a model of the real indoor air-conditioning unit from the catalogue data of a manufacturer, then built the model for the simulation of the internal sound propagation in the hotel room. The second step was to mock-up the real hotel room. The goal of the paper is to compare the calculated data from the simulations with the measured data in-situ.